Abuse of power in the disciplinary actions of a state psychology licensing board: inequitable outcomes and early career psychologists - Faber, Sonya C.; Wu, Edward; Bartlett, Amy (Frontiers in Psychology, 2023)
The field of psychology has established high professional standards which have become a cornerstone of the practice of psychology. However, powerful boards tasked with administering these standards can operate with little oversight, making it difficult to monitor whether these institutions are operating in a fair and impartial way. In particular, early-career psychologists who have less experience and power in their initial years of independent practice may be singularly vulnerable as they have relatively little experience to navigate the profession, including fielding complaints that may be made against them to a licensing board. While it is essential to ensure early-career psychologists are upholding their commitments to the practice, there are risks in policing their activities without orienting toward growth, learning, and professional development. Even the smallest disciplinary action may never be expunged from a psychologist’s record, resulting in long-term implications for insurance coverage, reputation and future professional viability in the field. Overly-punitive approaches can be distressing or even traumatizing. In this paper, we examine disciplinary actions of the Kentucky Board of Examiners of Psychology (KBEP) from the years 2000 to 2020 (N = 65) to determine the methodology by which the Board administers its oversight function. We analyze the nature of the discipline received (fines, suspensions, continuing education, supervision) revealing a two-tiered system of punishments, and provide context regarding the nature of the disciplinary process and its impacts. We report on qualitative interviews of early career psychologists subject to disciplinary actions by the Board, and psychologists who supervised early career psychologists investigated by the Board. We compare legislation governing KBEP and make comparisons to the workings of licensing boards in three other states. Using these findings, we make recommendations for revisions to the applicable legislation and administrative processes of the Board to establish an improved balance between public safety, the well-being of new psychologists, equity considerations such as race, and the development of the practice of psychology in Kentucky. This work brings to light previously unexamined injustices that can knowingly or unknowingly be perpetuated by licensing Boards, and can be used to inform the creation of more just, balanced and inclusive professional Boards.